Direct mechanical thrombectomy in tPA-ineligible and -eligible patients versus the bridging approach: a meta-analysis. (28th April 2018) - Kaesmacher, Johannes; Mordasini, Pasquale; Arnold, Marcel; López-Cancio, Elena; Cerdá, Neus; Boeckh-Behrens, Tobias; Kleine, Justus F; Goyal, Mayank; Hill, Michael D; Pereira, Vitor Mendes; Saver, Jeffrey L; Gralla, Jan; et al.
Abstract : Background: Whether pretreatment with intravenous thrombolysis prior to mechanical thrombectomy (IVT+MTE) adds additional benefit over direct mechanical thrombectomy (dMTE) in patients with large vessel occlusions (LVO) is a matter of debate. Methods: This study-level meta-analysis was presented in accord with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Pooled effect sizes were calculated using the inverse variance heterogeneity model and displayed as summary Odds Ratio (sOR) and corresponding 95% confidence interval (95% CI). Sensitivity analysis was performed by distinguishing between studies including dMTE patients eligible for IVT (IVT-E) or ineligible for IVT (IVT-IN). Primary outcome measures were functional independence (modified Rankin Scale≤2) and mortality at day 90, successful reperfusion, and symptomatic intracerebral hemorrhage. Results: Twenty studies, incorporating 5279 patients, were included. There was no evidence that rates of successful reperfusion differed in dMTE and IVT+MTE patients (sOR 0.93, 95% CI 0.68 to 1.28). In studies including IVT-IN dMTE patients, patients undergoing dMTE tended to have lower rates of functional independence and had higher odds for a fatal outcome as compared with IVT+MTE patients (sOR 0.78, 95% CI 0.61 to 1.01 and sOR 1.45, 95% CI 1.22 to 1.73). However, no such treatment group effect was found when analyses were confined to cohorts with a lower risk of selection bias (including IVT-E dMTE patients). Conclusion: The quality of evidence regarding the relative merits of IVT+MTE versus dMTE is low. When considering studies with lower selection bias, the data suggest that dMTE may offer comparable safety and efficacy as compared with IVT+MTE. The conduct of randomized-controlled clinical trials seems justified.